Programa educativo de aprendizaje servicio para la mejora de competencias en desarrollo personal ciudadanía y cívica en estudiantes de quinto grado de secundaria de la Institución Educativa Teniente Manuel Clavero Muga Punchana 2022 - Morey Araujo, Rossana (2024)
The research evaluated the effect of the educational program of service learning on the strengthening of personal development, citizenship, and civic competencies of fifth grade secondary students at the Teniente Manuel Clavero Muga Punchana Educational Institution during the year 2022. The question that guided the research was: What is the effect of the educational program of service learning on the development of these competencies in the students? An evaluative, quasi-experimental research with two groups, univariate and longitudinal was used. The sample consisted of 72 students, 32 in the experiment group and 40 as control group. The performance test was validated by expert judgment. The results indicated that the implementation of the educational program of service learning was effective to significantly improve the personal development, citizenship, and civic skills of fifth grade secondary students at the institution, at the end of the experimentation. The results showed that the experiment group had an overall average of 15.89, while the control group achieved an average of 13.19.